A competitividade na docência do ensino superior: o trabalho coletivo em utopia? - Breitenbach, Ilciane Maria Sganzerla (Universidade do Vale do Rio dos Sinos, 2015)
This study aimed to analyze the competitiveness in higher education, taking two Private Institutions located in Serra Gaúcha. The theoretical basis that support the research were mainly the contributions of Zygmunt Bauman, Richard Sennett and Pierre Bourdieu. The empirical research material held from interviews with nine professors working in two Institutions of Higher Education involved. The analytical exercise, carried out with the use of selected theoretical tools, showed, among other positions, the presence of competitiveness in academic areas, although it is acknowledged the advantages of living in collaborative environments. However, in practice, there are few conditions to these happen. The study also allowed to state that, in the view of professors, the increase and accumulation of activities, workload and recovery periods, contributes to the competitive processes. In the opinion of professors, one of the conditions for the collective work is instituted, involves investments in teacher education that besides favoring the technical aspects, it would constitute in sharing spaces among professors. The data showed that there are factors that are linked to competition and collaborating for it to occur. They mention those proper to the human nature, in addition to factors produced in the family structure, in school culture, in the institutional environment, and in the capitalist model of society, including the scientific field. However, it was possible to highlight, there are factors that enable collaborative phenomena, among them, the story of life of individuals, collaborative experiences of rupture with the dominant model, the positive interpersonal experiences, as well as the need to answer to the challenges of professional practice. It was observed a gap of reflections and proposals in this regard and it was the prospect that the study can mobilize new research about the subject in higher education.
Keywords: Competitividade; Docência; Ensino superior; Competitiveness; Teaching; Higher education; ACCNPQ::Ciências Humanas::Educação